2019
DOI: 10.1111/joim.13001
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of immune‐related gene expression in children with familial hypercholesterolaemia

Abstract: Background Innate and adaptive immune responses are pivotal in atherosclerosis, but their association with early‐stage atherosclerosis in humans is incompletely understood. In this regard, untreated children with familial hypercholesterolaemia may serve as a human model to investigate the effect of elevated low‐density lipoprotein (LDL)‐cholesterol. Objectives We aimed to study the immunological and inflammatory pathways involved in early atherosclerosis by examining mRNA molecules in peripheral blood mononucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
2
2
0
Order By: Relevance
“…Aggregation of LDL particles typically occurs following their retention in the arterial subendothelial intimal layer [1,2,[30][31][32], but our present results suggest that lipoproteins in FH subjects are primed for aggregation already while circulating in the blood, potentially due to their increased residence time in plasma caused by the underlying LDLR defect. In line with this, we previously showed that FH children have higher circulating levels of oxidized LDL [33] and display a shift in blood monocytes toward a more pro-inflammatory phenotype We also observed previously that peripheral blood mononuclear cells in FH children are characterized by a pro-inflammatory phenotype, which can be partially normalized upon initiation of statin treatment [34]. Along with the isolated hypercholesterolemia, these alterations in FH subjects could help explain their elevated risk of ASCVD [35][36][37].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Aggregation of LDL particles typically occurs following their retention in the arterial subendothelial intimal layer [1,2,[30][31][32], but our present results suggest that lipoproteins in FH subjects are primed for aggregation already while circulating in the blood, potentially due to their increased residence time in plasma caused by the underlying LDLR defect. In line with this, we previously showed that FH children have higher circulating levels of oxidized LDL [33] and display a shift in blood monocytes toward a more pro-inflammatory phenotype We also observed previously that peripheral blood mononuclear cells in FH children are characterized by a pro-inflammatory phenotype, which can be partially normalized upon initiation of statin treatment [34]. Along with the isolated hypercholesterolemia, these alterations in FH subjects could help explain their elevated risk of ASCVD [35][36][37].…”
Section: Discussionsupporting
confidence: 76%
“…In line with this, we previously showed that FH children have higher circulating levels of oxidized LDL [33] and display a shift in blood monocytes toward a more pro-inflammatory phenotype [18]. We also observed previously that peripheral blood mononuclear cells in FH children are characterized by a pro-inflammatory phenotype, which can be partially normalized upon initiation of statin treatment [34]. Along with the isolated hypercholesterolemia, these alterations in FH subjects could help explain their elevated risk of ASCVD [35][36][37].…”
Section: Discussionsupporting
confidence: 72%
“…In line with this, we previously showed that FH children have higher circulating levels of oxidized LDL (29) and display a shift in blood monocytes towards a more proinflammatory phenotype (12). We also observed previously that peripheral blood mononuclear cells (PBMCs) in FH children are characterized by a pro-inflammatory phenotype, which can be partially normalized upon initiation of statin treatment (30). Along with the isolated hypercholesterolemia, these alterations in FH subjects could help explain their elevated risk of ASCVD (31)(32)(33).…”
Section: Discussionmentioning
confidence: 76%
“…In line with this, we previously showed that FH children have higher circulating levels of oxidized LDL (29) and display a shift in blood monocytes towards a more proinflammatory phenotype (12). We also observed previously that peripheral blood mononuclear cells (PBMCs) in FH children are characterized by a pro-inflammatory phenotype, which can be partially normalized upon initiation of statin treatment (30). Along with the isolated hypercholesterolemia, these alterations in FH subjects could help explain their elevated risk of ASCVD (31)(32)(33).…”
Section: Discussionmentioning
confidence: 76%